PEMBUATAN BIOPORI RESAPAN AIR HUJAN DI RT 09 RW 04 KEL.TUNJUNGSEKAR, KEC.LOWOKWARU KOTA MALANG - Kasijanto Kasijanto; Sadar Wahjudi; Heryanto Heryanto; Listiyono Listiyono; Kris Witono (Publisher UPT P2M Politeknik Negeri Malang, 2019)
Kelurahan Tunjungsekar is one of District in Malang, which is located at center of town that it has rarely have a water absorbtion region so it is prone to flooding when it rains. Through this PkM program, it is proposed a biopori production that serves as a water catchment area which can help the land or residental areas that have rarely trees to absorb water in a relatively short time so that no water flows or even floods occur. The method of implementation of this program is to invite people to make biopori at some point which is prone to puddle. Some stages of the implementation of this biopori making program are: 1. The preparation stage, at this stage preparation of equitment and biopori media and site survey to determine which points need to be installed biopori. 2. Implementation phase, at this stage people do soil drilling and installation of biopori at some point location that has been predetermined. Reporting stage, at this stage will be reported the results of activities that have been implemented including details of the cost. The whole stages are conducted over a period of 8 months involving the role of the civilitation RT.09 RW.04 Kel. Tunjungsekar Kec. Lowokwaru Kota Malang.